Public service delivery, exclusion and externalities: Theory and experimental evidence from india - Alex Armand; Britta Augsburg; Antonella Bancalari; Maitreesh Ghatak (Institute for Fiscal Studies (IFS), 2023)
This study explores the interaction between the quality of public services, the implementation of user fees, and the resulting potential for exclusion, that can lead to negative externalities. Our theoretical framework takes account of the possible externalities that result from excluded users accessing alternative options in the context of sanitation, i.e., open defecation, and challenges the conventional wisdom that higher quality unequivocally leads to increased use. Instead, it highlights the ambiguity that results from a simultaneous increase in usage due to improved services (quality effect) and a decrease caused by the fees (price-elasticity effect). We then provide empirical evidence from a randomized controlled trial, where we incentivized the quality of water and sanitation services in the two largest cities of Uttar Pradesh, India. We show that higher service quality increases fee compliance but excludes some users, leading to unintended negative health externalities. Our detailed data provides evidence that results are driven by changes in caretaker behaviour. This finding highlights the need to be cautious regarding user fees, especially for public services involving significant externalities, and in settings where the users are very poor.
Keywords: C93; H40; I15; Q53; 330; public service; exclusion; externality; maintenance; user fees; payment; water and sanitation; health